2006
DOI: 10.1063/1.2403127
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity, Raman, and Brillouin scattering studies of M2O–MgO–WO3–P2O5 glasses (M=K,Rb)

Abstract: The authors report the results of temperature-dependent Brillouin scattering from both transverse and longitudinal acoustic waves, heat capacity studies as well as room temperature Raman scattering studies on M 2 O-MgO-WO 3 -P 2 O 5 glasses ͑M=K,Rb͒. These results were used to obtain information about structure and various properties of the studied glasses such as fragility, elastic moduli, ratio of photoelastic constants, and elastic anharmonicity. They have found that both glasses have similar properties but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…30,31 In Figure 10 we show that a 5/3 slope describes adequately the data below 140 K yielding A 2.4 GPa or A/ρ 3 × 10 6 m 2 /s 2 similar to what found in glycerol 32 and in a variety of glass formers 30 but definitely larger than the value found in some phosphate glasses. 31 Finally, as far as the zero frequency bulk modulus is concerned, we wish to point out that although we have assumed K ∞ − K 0 to be constant and equal to its low temperature limit of ∼0.55 GPa, we can reasonably assume this quantity de-creases smoothly with increasing temperature so that K ∞ (T ) K 0 (T ) + 0.55 GPa (19) and consequently M ∞ (T ) K 0 (T ) + 4 3 G ∞ (T ) + 0.55 GPa. (20) The validity of this upper limit can in principle be checked performing higher frequency scattering experiments such as inelastic x-ray or neutron scattering from which M ∞ (T) is directly measured.…”
Section: Discussionsupporting
confidence: 75%
“…30,31 In Figure 10 we show that a 5/3 slope describes adequately the data below 140 K yielding A 2.4 GPa or A/ρ 3 × 10 6 m 2 /s 2 similar to what found in glycerol 32 and in a variety of glass formers 30 but definitely larger than the value found in some phosphate glasses. 31 Finally, as far as the zero frequency bulk modulus is concerned, we wish to point out that although we have assumed K ∞ − K 0 to be constant and equal to its low temperature limit of ∼0.55 GPa, we can reasonably assume this quantity de-creases smoothly with increasing temperature so that K ∞ (T ) K 0 (T ) + 0.55 GPa (19) and consequently M ∞ (T ) K 0 (T ) + 4 3 G ∞ (T ) + 0.55 GPa. (20) The validity of this upper limit can in principle be checked performing higher frequency scattering experiments such as inelastic x-ray or neutron scattering from which M ∞ (T) is directly measured.…”
Section: Discussionsupporting
confidence: 75%
“…Poisson's ratio, σ, is defined as the ratio between the transverse contraction strain and longitudinal extension strain in a stretched bar. Previous studies of the relation of the Poisson's ratio with the glass structure showed that it was greater than 0.25 when the ions themselves are deformed under stress in addition to the network distortion [28,29]. The alkali content dependences of Poisson's ratio, σ, of the single-alkali borate glasses are shown in Figure 6b.…”
Section: Poisson's Ratiomentioning
confidence: 88%
“…However, most glasses are far from the central potential and the Cauchy relation, L = 3µ. The Cauchy-type relation, L = A + Bµ with B~3, was reported to hold for the high frequency limit values of the L and the µ for some types of glasses, where A is the material dependent constant [29,33].…”
Section: Cauchy-type Relationmentioning
confidence: 99%
“…The number of independent elastic constants is only two, namely, the longitudinal (L or c 11 ) and the shear (G or c 44 ) modulus, where c 11 and c 44 are the elastic stiffness constants in isotropic systems. Additional local symmetry conditions 32) The studied oxide glasses were characterized by relatively weak elastic anharmonicity in comparison with polymer glasse, that have higher fragility. Such difference obeys the correlation between the fragility and the Grüneisen parameters, since the anharmonisity increases as the fragility increases.…”
Section: Cauchy Type Relation Of Amber At High Pressuresmentioning
confidence: 99%